A qualitative exploration of information-seeking by electronic nicotine delivery systems (ENDS) users in New Zealand - Robertson, Lindsay (BMJ Open, 2018)
OBJECTIVES: Given recent increases in awareness and uptake of electronic nicotine delivery systems (ENDS), we aimed to explore ENDS users’ information needs and search behaviours and whether information gaps exist. DESIGN: Qualitative study using semistructured interviews that probed participants’ smoking behaviours and ENDS use; data in this study examine ENDS information-seeking behaviours. We used qualitative description to analyse interview transcripts. PARTICIPANTS AND SETTING: We recruited 39 current ENDS users (20 dual users and 19 exclusive ENDS users who reported having previously smoked cigarettes regularly) aged 18 and over, from three urban centres in New Zealand. RESULTS: Several participants used Google to search for information on ENDS’ health effects, but described the material they retrieved as vague or contradictory. Some interpreted the absence of information on long-term health effects as evidence ENDS did not pose potential health risks, and several perceived e-liquids as benign. Many relied on information sourced from other ENDS users, gleaned from online forums, YouTube or from discussions with friends and acquaintances; these sources typically presented ENDS positively. Several participants found specialist ENDS retailers provided valuable advice; non-specialist store staff generally lacked detailed product knowledge and sometimes offered inaccurate information. CONCLUSION: People seeking information on ENDS’ health effects are more likely to retrieve recommendations, product reviews and endorsements from online sources or through exchanges with other users, than they are to find scientific data. Health authorities could help meet potential users’ information needs by, first, creating and frequently updating objective lay summaries of the latest scientific evidence; second, by mandating licensing for retailers with guidelines to disclose uncertainty over ENDS’ efficacy for cessation and longer-term health effects, and the need for complete substitution of ENDS for combustible cigarettes among those who use these products.